Etude Ethnobotanique, Evaluation De L’activite Antifongique Sur Candida Albicans Et De La Toxicite Sur Des Cellules Hff De Bersama Abyssinica (Fresen.), Une Plante De La Pharmacopee Ivoirienne - Djeneb Camara; Kouadio Bene; Goueh Gnahoue; N’guessan Bra Yvette Fofie; Guédé Noël Zirihi (European Scientific Journal, ESJ, 2016)
To make a contribution to the fight against opportunistic mycoses in sharp increase in AIDS patients, we conducted an ethnobotanical investigation in the Department of Transua (Côte d’Ivoire). This investigation has shown that the plant Bersama abyssinca is the most used in the treatment of skin infection. Our team tested different extracts of leaves of B. abyssinica (aqueous extract total (ETA), 70% ethanol extract (EE70%) and aqueous extract residual (ERA)) on the in vitro growth of Candida albicans, to determine some inhibitions parameters. These three extracts were active in C. albicans, with respective IC50: 160 μg/ml for ETA, 100 μg/ml for EE70% and 55 μg/ml for ERA. We found that B. abyssinica is not toxic for human cells HFF, on the contrary, it increases the proliferation of dividing cells thereby improving defense mechanisms.